2019
DOI: 10.1016/j.ophtha.2019.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Characteristics of East Asian Patients with Occult Macular Dystrophy (Miyake Disease)

Abstract: study group zPurpose: To describe the clinical and genetic characteristics of the cohort enrolled in the East Asian studies of occult macular dystrophy (OMD).Design: International, multicenter, retrospective cohort studies.Participants: A total of 36 participants from 21 families with a clinical diagnosis of OMD and harboring pathogenic RP1L1 variants (i.e., Miyake disease) were enrolled from 3 centers in Japan, China, and South Korea.Methods: A detailed history was obtained, and comprehensive ophthalmological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 32 publications
3
59
2
Order By: Relevance
“…In this cohort, visual acuity varied widely from 0.04 to 0.5; however, no significant correlation was found between visual acuity and onset and duration, unlike the results of previous studies. 4,8 This may be related to the small number of patients included in this study. Another limitation of our study is that it is a cross-sectional retrospective study, and more accurate data regarding disease progression could not be obtained.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In this cohort, visual acuity varied widely from 0.04 to 0.5; however, no significant correlation was found between visual acuity and onset and duration, unlike the results of previous studies. 4,8 This may be related to the small number of patients included in this study. Another limitation of our study is that it is a cross-sectional retrospective study, and more accurate data regarding disease progression could not be obtained.…”
Section: Discussionmentioning
confidence: 94%
“…The vari-ant p.S1199C is not found in the ExAC or 1000 Genomes Project database, but all 12 reported patients harboring this variant were East Asian. 4,19,20 This indicated that these two variants were more common in the East Asian population than in other populations. Previous studies showed that the penetrance of the variant p.R45W was incomplete, ranging from 38% to 85%.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations